The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1038/s41440-021-00710-5
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of pendrin in urinary extracellular vesicles in a rat model of aldosterone excess and in human primary aldosteronism

Abstract: Pendrin is a Cl−/HCO3− exchanger selectively present in the intercalated cells of the kidney. Although experimental studies have demonstrated that pendrin regulates blood pressure downstream of the renin-angiotensin-aldosterone system, its role in human hypertension remains unclear. Here, we analyzed the quantitative changes in pendrin in urinary extracellular vesicles (uEVs) isolated from a total of 30 patients with primary aldosteronism (PA) and from a rat model of aldosterone excess. Western blot analysis r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 52 publications
0
18
0
Order By: Relevance
“…In the mouse, apical plasma membrane pendrin abundance is low under basal conditions but increases ≈6-fold in response to aldosterone. 11 Ochiai-Homma et al 87 quantified pendrin abundance in human urinary extracellular vesicles as an index of renal pendrin abundance and showed that aldosterone upregulates pendrin in human kidney, consistent with observations in mouse. Moreover, they showed a strong correlation between pendrin abundance in these human urinary extracellular vesicles and serum aldosterone concentration.…”
Section: Regulation Of Pendrin By Aldosteronementioning
confidence: 56%
See 2 more Smart Citations
“…In the mouse, apical plasma membrane pendrin abundance is low under basal conditions but increases ≈6-fold in response to aldosterone. 11 Ochiai-Homma et al 87 quantified pendrin abundance in human urinary extracellular vesicles as an index of renal pendrin abundance and showed that aldosterone upregulates pendrin in human kidney, consistent with observations in mouse. Moreover, they showed a strong correlation between pendrin abundance in these human urinary extracellular vesicles and serum aldosterone concentration.…”
Section: Regulation Of Pendrin By Aldosteronementioning
confidence: 56%
“…87 Following either adrenalectomy or MR antagonist administration, pendrin abundance in urinary vesicles fell substantially. 87 Therefore, in rodents and in humans, aldosterone greatly stimulates pendrin abundance in the kidney, which occurs, at least partly, through the alkalosis it generates. 88 Aldosterone increases apical plasma membrane pendrin expression in tandem with increased pendrin-mediated Cl − absorption and HCO 3 − secretion.…”
Section: Regulation Of Pendrin By Aldosteronementioning
confidence: 99%
See 1 more Smart Citation
“…Exosomes may serve as biomarkers of MR activity. Ochiai-Homma et al [ 159 ] focused on pendrin, a Cl – /HCO3 – exchanger that is only expressed by renal intercalated cells. In a rat model, the pendrin level in the urinary exosome was reduced by therapeutic interventions favored for PA patients; the urinary level was correlated with the renal level.…”
Section: A New Era Of Progress In Primary Aldosteronism Treatment: Mi...mentioning
confidence: 99%
“…Interestingly, the literature has demonstrated a role for exosomes in physiological and pathological conditions, such as in the progression of cancer, which has been vastly described in the literature [ 17 , 18 , 19 , 20 ]. In addition, circulating and urinary exosomes are being used to identify key proteins and microRNA (miRNAs), circular RNAs (circRNA), or long non-coding RNA (lncRNA) associated with different diseases including type 2 diabetes, nephropathy, aldosteronism, atherosclerosis, and several types of cancer (bladder, gastric, prostate cancers) [ 21 , 22 , 23 , 24 , 25 ]. Therefore, it seems that the exosomes carry potential molecules to help in the diagnosis of diseases.…”
Section: Exosomesmentioning
confidence: 99%